Aktiengesetz, Band 3/1, §§ 53a-66 Großkommentar - Arnold, Michael 1969-; Gehrlein, Markus 1957-; Henze, Hartwig 1938-2024; Notz, Richard L.; Steffek, Felix 1975- (De Gruyter, 2021)
Excellent scholarship, steeped in tradition: the fifth edition of this comprehensive commentary on the Stock Corporation Act unites academic rigor with practical utility. In fifteen volumes, the authorial team, composed of renowned experts from academia and legal practice, examines the Stock Corporation Act and relevant secondary legislation. Volume 3/1 contains commentary on §§ 53a-66 AktG.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 10. Jan 2022)
Keywords: Deutschland -- Aktiengesetz; Aktiengesetz; LAW / Securities; Kommentar